‘Cya IRL’: Researching digital communities online and offline - Abidin, Crystal (University of Western Australia, 2013)
This article is a reflexive account of an ethnographer's foray into digital anthropology, necessitating the formulation of collaborative research strategies. The information presented comes from yearlong fieldwork among blogshop owners and commercial bloggers in Singapore. This paper is part of an ongoing doctoral dissertation that looks into narratives of self-creation, boundaries of privacy, and vicarious consumption, and is the groundwork for the continuation of more extensive and in-depth research.